WILAYAH JELAJAH DAN TERITORI OWA JAWA (Hylobates moloch) DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK - Mia Clarissa Dewi; Ani Mardiastuti; Entang Iskandar (Media Konservasi, 2016)
Javan gibbon is endemic and endangered primate of Java. The research aims to map home ranges and territories of three habituated javan gibbons (Goup A, B and S) in Gunung Halimun-Salak National Park from March to July 2015. This finding will support the conservation management for javan gibbon. The mapping of those areas was determined by following the groups for 541 hours and analyzed the data using minimum convex polygon. The home range average of the three groups was 33,41 ha (Group A = 23,7 ha; B = 43,8 ha; and S = 32,7 ha). The largest home range had the lowest food tree densities (50 ind/ha). The average of territory was 0,57 ha (Group A = 0,4 ha; B = 0,8 ha; and S = 0,4 ha). The territory areas had food tree densities in higher (116,7 ind/ha) compare to the home ranges (76,7 ind/ha). The large territory area had low food tree densities (90 ind/ha), otherwise the small territory area had high food densities (Group A 160 ind/ha; Group S 110 ind/ha).Keywords: habitat, home range, javan gibbon, territory